Brazing of porous copper foam/copper with amorphous Cu-9.7Sn-5.7Ni-7.0P (wt%) filler metal: interfacial microstructure and diffusion behavior - Zahri, Nur Amirah Mohd; Yusof, Farazila; Miyashita, Yukio; Ariga, Tadashi; Haseeb, A.S. Md. Abdul; Jamadon, Nashrah Hani; Sukiman, Nazatul Liana (Springer Verlag (Germany), 2020)
In this work, brazing of porous copper foam (PCF) to copper (Cu) using amorphous Cu-9.7Sn-5.7Ni-7.0P (in weight, wt%) filler metal has been performed. PCF with different pore densities of 15 pore per inch (PPI), 25 PPI, and 50 PPI were sandwiched in between amorphous Cu-9.7Sn-5.7Ni-7.0P filler/Cu based plate. A brazed joint of Cu/Cu using amorphous Cu-9.7Sn-5.7Ni-7.0P filler was prepared for comparison purposes. The interfacial microstructures and mechanical properties of the brazed joint were investigated to study the joint ability after the brazing process. Scanning electron microscope (SEM) confirmed the interfacial microstructure by the formation of the diffusion layer (shown in light shaded area) and filler layer (gray island-shaped) for both Cu/Cu and Cu/PCF/Cu brazed joint. The X-ray diffraction (XRD) patterns identified the brittle phases of Cu3P and Ni3P, Cu and Cu6Sn5 phases at the diffusion layer. In the shear test, the strength value decreases with increase in the pore densities of PCF. The decreasing shear strength observed with an increase in the number of PPI in PCF is due to the formation of more cavities in Cu/PCF as the number of PPI in Cu/PCF increases. © 2019, International Institute of Welding.